Does Philips On The Right Track? - Sari Wahyuni; Monica Devina; Aryo Andrashmara; Muhammad Zuhdi; Putra Ramadisia; Sania Humaira (AIBPM Publisher, 2018)
In the dynamic environment, a global company is required to develop strategic management of their business as the foundation to establish the competitive advantages. Therefore, the main purpose of this paper is to analyze the strategic management implemented on Koninklijke Philips N.V or Philips, a diversified technology company which focuses on improving people’s lives through meaningful innovation in the areas of Healthcare, Consumer Lifestyle and Lighting. The strategies are developed at corporate, business, and functional level, and should be aligned to attain the goals. Moreover, the research method used secondary data including annual reports, statistics, and other official reports. The results show that generic differentiation is the right track for Philips through improving innovation and R&D performance. Keywords: competitive advantage,differentiation strategy,global company, innovation, strategic management